EL BORO Y EL MUNDO ARN - Laos, Roberto (2019)
Besides its multiple commercial uses, borate minerals have been recently of great interest for researchers seeking for an explanation to the origin of life on Earth. The largest borate mineral deposit in Peru is located in a salt flat in the Arequipa province.